2011
DOI: 10.1177/0018720811405196
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Head-Mounted Displays and Their Effects on Simulator Sickness

Abstract: To reduce the occurrence of SS, a degree of peripheral vision of the external world should be provided. Furthermore, users and designers should be aware that head movement behavior may be affected by HMD characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
146
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(156 citation statements)
references
References 59 publications
8
146
1
1
Order By: Relevance
“…Currently the evidence about whether display lag contributes to cybersickness in HMDs appears to be mixed. While some researchers have found that increasing display lag also increases cybersickness [45,46], others have found no significant change [8,14]. However, these apparently discrepant findings might reflect study-based differences in the detectability of lag 1 -since baseline system lag, additional display lag, and the types of head movements studied, often varied markedly from study-tostudy.…”
Section: Relationship Between Head-movements and Cybersickness In Hmdsmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently the evidence about whether display lag contributes to cybersickness in HMDs appears to be mixed. While some researchers have found that increasing display lag also increases cybersickness [45,46], others have found no significant change [8,14]. However, these apparently discrepant findings might reflect study-based differences in the detectability of lag 1 -since baseline system lag, additional display lag, and the types of head movements studied, often varied markedly from study-tostudy.…”
Section: Relationship Between Head-movements and Cybersickness In Hmdsmentioning
confidence: 99%
“…Early findings (using fixed-based simulators rather than HMDs) suggested that traditional vection might be a prerequisite for visually induced motion sickness in stationary observers [25]. However, while fixed-base simulator studies have often reported positive correlations between vection and visually induced motion sickness [14,[31][32][33], other studies appeared to suggest negative relationships between the two phenomena [34], and still others failed to find significant relationships between them [4,28,[35][36][37].…”
Section: Relationship Between Vection and Cybersickness In Hmdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, studies have been conducted to analyze whether the user's posture while viewing VR contents or the visual elements transmitted via the HMD are interfering with the immersion experience [26][27][28][29][30]. When approaching with the same concept, the user interface can be an important factor in increasing immersion and convenience; nevertheless, it may even be a factor that causes motion sickness and the like.…”
Section: Related Workmentioning
confidence: 99%